PTH-324 Quality of life outcomes following pelvic exenteration and abdominoperineal resection: a prospective comparison study. (22nd June 2015) - Radwan, R; Jones, H; Codd, R; Evans, M; Davies, M; Harris, D; Beynon, J
Abstract : Introduction: The literature surrounding quality of life in patients undergoing pelvic exenteration is limited. Furthermore, there remains no similar matched comparisons with patients undergoing abdominoperineal resection. The EORTC QLQ-C30 is a validated cancer specific questionnaire that can be used for patients undergoing rectal cancer resection. Our aim was to evaluate and compare differences in long term quality of life for patients with rectal cancer undergoing both abdominoperineal resection and pelvic exenteration at our institute. Method: All consecutive patients that had undergone either abdominoperineal resection or pelvic exenteration between January 2011 and December 2012 were included in the study. Patient demographics, tumour characteristics, intra-operative details and postoperative outcomes were collected. Patients were asked to complete the EORTC QLQ-C30 questionnaire at baseline (prior to surgery) and at two weeks post-operatively. Subsequent questionnaires were then requested at 3, 6, 12 and 24 months following operation. Results: A total of 120 patients were included in the study; 60 patients underwent abdominoperineal resection and 60 patients had pelvic exenteration. This cohort consisted of 62 men and 58 women with a median age of 68 (range 31- 89) years. The majority of functional and symptom scale differences were only noted within the first 2 weeks postoperatively with levels being comparable for both groups from 3 months following surgery. Only financial worries remained considerably higher in patients undergoing exenteration for up to 24 months postoperatively. For overall global health status, a significant difference was again only identified 2 weeks postoperatively (p = 0.032), with those patients undergoing exenteration experiencing a lower overall level. From 3 months following surgery, no further differences were identified. Conclusion: This is one the largest longitudinal observational studies looking at quality of life in patients undergoing pelvic exenteration and the first to compare these patient outcomes against a matched APER group. Here we have shown that the length of time it takes for these patients to reach a quality of life similar to that of their counterpart APER group is not dissimilar. These data will undoubtedly help counsel patients about recovery times and will guide informed decision making in the future. Disclosure of interest: None Declared.